New Records of the Egg Development Phase of Varuna litterata in the Lower Serayu River, Central Java - sinaga, sorbakti; Widodo , Maheno Sri; Maimunah, Yunita (Department of Aquaculture, 2024)
One of the Brachyura crabs found in the lower reaches of the Serayu River is Varuna litterata, also known as the